(untitled) (Revista de Ciências Agroveterinárias, 2013)
This study aimed to show the variations in the quality of corn used in the poultry industry and how it can act on poultry performance. Currently, the Brazilian poultry industry is considered a highly technical and competitive activity, with high rates of productivity and supply of high quality products and low cost. Corn holds more than 60% of total grains used in diets for broilers and laying hens, the under Brazilian conditions, showing great variation in their nutritional composition, which is usually neglected. The grains have poor nutritional value affected by chemical composition changes, decreased bioavailability of some nutrients, and presence of anti-nutritional factors and proliferation of fungi with or without production of mycotoxins. As an alternative to improving the nutritional quality of foods used in feeding of poultry, mainly from corn, currently production lines for rations of deployment of new technologies such as density or gravity table and the utilization of prediction equation with classification and density of grains.